Sines breakwater harbour: the OSOM+ monitoring program - E.M. Fortes, Conceição Juana; Capitao, Rui; Lemos, Rute; Neves, Maria Graça; Silva, Luis Gabriel; Henriques, Maria João; Henriques, Maria João; Martins, Tiago (Italian journal of engineering geology and environment, 2020)
<span data-sheets-value="{"1":2,"2":"The current program of Systematic Observation of Maritime Works (OSOM+), under development at the National Laboratory for Civil Engineering (LNEC), is essentially applied to rubble mound breakwaters. The OSOM’s main objective is to monitor the behaviour of maritime structures under inspection and recommend timely interventions for their maintenance and/or repair as to properly maintain its function during its lifetime. There are four main components of the OSOM+ program, namely: the periodic visual inspections made by a trained technician, where a set of photos and videos are taken at notable points along the structure and there is an identification of the main focuses of degradation of the structure; the periodic aerial inspections with an unmanned aerial vehicle (UAV) or drone, where individual aerial photographs are captured in a regularpattern and in the vertical direction, and from them orthomosaics, point clouds and/or profiles are obtained; the ANOSOM_WEB-based online platform, to store and/or query obtained information on the observation campaigns, as well as to diagnose present, evolution and risk conditions of the structure; and a mobile, portable, application for real-time input and visualization of the database information. This paper presents an application of the OSOM+ program to the study case: the west breakwater of the port of Sines"}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The current program of Systematic Observation of Maritime Works (OSOM+), under development at the National Laboratory for Civil Engineering (LNEC), is essentially applied to rubble mound breakwaters. The OSOM’s main objective is to monitor the behaviour of maritime structures under inspection and recommend timely interventions for their maintenance and/or repair as to properly maintain its function during its lifetime. There are four main components of the OSOM+ program, namely: the periodic visual inspections made by a trained technician, where a set of photos and videos are taken at notable points along the structure and there is an identification of the main focuses of degradation of the structure; the periodic aerial inspections with an unmanned aerial vehicle (UAV) or drone, where individual aerial photographs are captured in a regularpattern and in the vertical direction, and from them orthomosaics, point clouds and/or profiles are obtained; the ANOSOM_WEB-based online platform, to store and/or query obtained information on the observation campaigns, as well as to diagnose present, evolution and risk conditions of the structure; and a mobile, portable, application for real-time input and visualization of the database information. This paper presents an application of the OSOM+ program to the study case: the west breakwater of the port of Sines